2017
DOI: 10.1016/j.tibs.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Cdc20: At the Crossroads between Chromosome Segregation and Mitotic Exit

Abstract: Cell-division cycle protein 20 homologue (Cdc20) has important functions in chromosome segregation and mitotic exit. Cdc20 is the target of the spindle assembly checkpoint (SAC) and a key cofactor of the anaphase-promoting complex or cyclosome (APC/C) E3 ubiquitin ligase, thus regulating APC/C ubiquitin activity on specific substrates for their subsequent degradation by the proteasome. Here we discuss the roles of Cdc20 in SAC signalling and mitotic exit, describe how the integration of traditional approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 91 publications
(110 reference statements)
4
113
0
Order By: Relevance
“…1 Our findings may be relevant to the design of ad hoc therapeutic strategies that take advantage of aneuploid cell dependency on chaperone pathways, protein turnover, heightened metabolism, and a deregulated cell cycle. 50 CDC20 is also a promising target for anticancer therapies, 51 and preclinical data suggest that chemical inhibition of APC/C alone or in combination with topoisomerase poisons 52 or defective sister chromatid cohesion 53 may be explored as potential synthetic lethal strategies under the aneuploid condition. Novel biological insights into disease mechanisms, such as those obtained in our study, could boost the development of new personalized medicinebased trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Our findings may be relevant to the design of ad hoc therapeutic strategies that take advantage of aneuploid cell dependency on chaperone pathways, protein turnover, heightened metabolism, and a deregulated cell cycle. 50 CDC20 is also a promising target for anticancer therapies, 51 and preclinical data suggest that chemical inhibition of APC/C alone or in combination with topoisomerase poisons 52 or defective sister chromatid cohesion 53 may be explored as potential synthetic lethal strategies under the aneuploid condition. Novel biological insights into disease mechanisms, such as those obtained in our study, could boost the development of new personalized medicinebased trials.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate strategies include a combination of microtubule depolymerizing drugs and PLK1 inhibitors, which drove BCL2 inactivation in a rhabdomyosarcoma model, 48 dual topoisomerase I and CHK1 inhibition, which achieved a curative response in the context of decreased expression of RAD50 in carcinoma, 49 and simultaneous targeting of glycolytic metabolism and Aurora kinases, which killed AML cells. 50 CDC20 is also a promising target for anticancer therapies, 51 and preclinical data suggest that chemical inhibition of APC/C alone or in combination with topoisomerase poisons 52 or defective sister chromatid cohesion 53 may be explored as potential synthetic lethal strategies under the aneuploid condition.…”
Section: Discussionmentioning
confidence: 99%
“…CDC20 encodes cell division cycle 20, which is a regulator of cell cycle checkpoints. It binds directly to another regulatory factor, Cdh1, and activates the late mitotic promoting complex APC, which plays an important role in late-stage of cell division and withdrawal from mitosis [33, 34]. Recently, an increasing number of studies have shown that CDC20 is a carcinogenic factor that is widely regulated in a variety of human malignancies, including lung cancer, kidney cancer and prostate cancer.…”
Section: Disscusionmentioning
confidence: 99%
“…The SAC regulates metaphase to anaphase transition preventing entry into anaphase until all sister kinetochores are attached to the microtubules from opposite spindle poles ensuring the fidelity of chromosome segregation (Lara-Gonzalez et al, 2012;Dou et al, 2019). Several SAC components such as MAD1, MAD2, MAD3/BUBR1, BUB1, and BUB3 are localized to unattached kinetochores and participate in a signaling network that leads the inhibition of the E3 ubiquitin ligase anaphase promoting complex/cyclosome (APC/C) through recruiting CDC20, an activation factor of the APC/C (Kapanidou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%